2023
DOI: 10.11594/ijmaber.04.06.28
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and Employers’ Perceptions of Employability Skills in Uganda

Elvaida Agnes Tagulwa,
Philip Owino,
Francis Muwonge
et al.

Abstract: The study evaluated employability skills as they were perceived by students of Kyambogo University and employers. The population comprised of students and employers. Students were from the faculty of science and the sample size consisted of 226 students from six departments. The employers were from organisations where these students do their industrial training. The sample size of the employers consisted of 19 participants from thirteen organisations. The specific objective of the study was to evaluate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…İstihdam edilebilir olmayı sağlayan istihdam edilebilirlik becerileri belli bir işe özgü olmayıp yatay olarak tüm endüstri kollarını dikey olarak ise tüm işleri kapsayan becerilerdir (Tagulwa , Owino, Muwonge ve Kaahwa, 2023, s. 2039. Söz konusu becerilerin geliştirilmesinde ve mesleki yeterliliklerin kazandırılmasında ise mesleki eğitim programlarının önemli bir rolü bulunmaktadır.…”
Section: Introductionunclassified
“…İstihdam edilebilir olmayı sağlayan istihdam edilebilirlik becerileri belli bir işe özgü olmayıp yatay olarak tüm endüstri kollarını dikey olarak ise tüm işleri kapsayan becerilerdir (Tagulwa , Owino, Muwonge ve Kaahwa, 2023, s. 2039. Söz konusu becerilerin geliştirilmesinde ve mesleki yeterliliklerin kazandırılmasında ise mesleki eğitim programlarının önemli bir rolü bulunmaktadır.…”
Section: Introductionunclassified
“…Employers worldwide call for higher education to prioritize providing students with the work readiness skills to compete in the 21st-century workforce. Recent international surveys identified significant gaps between the skills students gain in college and those necessary to obtain employment (Rakowska & de Juana-Espinosa, 2021; Tagulwa et al, 2023). For example, in Italy, Succi and Canovi (2020) found that only 35% of students self-reported their employability skills matched those sought by employers.…”
Section: Introductionmentioning
confidence: 99%